Asymmetric syntheses of the 1-hydroxymethyl-2-hydroxy substituted pyrrolizidines (−)-macronecine, (−)-petasinecine, (−)-1-epi-macronecine, (+)-1-epi-petasinecine and (+)-2-epi-rosmarinecine - Brambilla, M; Davies, S; Fletcher, A; Roberts, P; Thomson, J (Elsevier, 2016)
The asymmetric syntheses of all four possible diastereoisomeric 1-hydroxymethyl-2-hydroxy substituted pyrrolizidines, (−)-macronecine, (−)-petasinecine, (−)-1-epi-macronecine and (+)-1-epi-petasinecine, are reported. Conjugate addition of lithium (S)-N-benzyl-N-(α-methylbenzyl)amide to tert-butyl (E)-hepta-2,6-dienoate, followed by aldol reaction with acrolein under various conditions gave four possible diastereoisomeric β-amino esters with the required stereogenic centres installed. In each case, the pyrrolizidine scaffold was rapidly accessed by reduction of the ester moiety followed by a sequential two-step protocol involving ozonolysis and hydrogenolysis/double reductive cyclisation. Following this route, (−)-macronecine, (−)-petasinecine, (−)-1-epi-macronecine and (+)-1-epi-petasinecine were synthesised in 21, 14, 10 and 19% overall yield, respectively, in six steps or fewer from commercially available starting materials. An analogous strategy employing enantiopure tert-butyl (R,E)-4-(triethylsilyloxy)hepta-2,6-dienoate facilitated the asymmetric synthesis of (+)-2-epi-rosmarinecine in 21% overall yield and >99:1 dr, in 13 steps from commercially available starting materials.